Effect Of Prrolonged Exposure To Extremely Low Frequency Electromagnetic Field On Plasma Cortisol, Glucose, Cholesterol And Triglycerides In Male Rats (Applied Biological Research, 2011)
Extremely low frequency electromagnetic fields (EMFs) produce both  positive and negative effects on biological processes and the present study  was aimed to evaluate the effect of low frequency EMF on some  biochemical parameters in rats. Forty five rats in 3 groups viz., control  group (kept under normal conditions in animal room), group 2 (exposed  for 135 days and under 50 Hz, 1 mT emitted from solenoid for 24 h daily),  and group 3 (sham group kept under conditions similar to group 2, except in off solenoid). Blood samples were collected to determine the concentration of cortisol, glucose, cholesterol and triglycerides in plasma.  In EMF exposed group plasma levels of cortisol, glucose, cholesterol and  triglyceride were significantly lower than those of other groups revealing  that long term exposure to EMF has potential clinical use with no  immunosuppressive effect.
Keywords: Colesterol; cortisol; electromagnetic field; glucose; long term exposure; rat; triglycerides